மரபிலக்கண நூல்களில் இடைச்சொற்களின் அமைப்பு முறை / Structure of Interjections in Traditional Grammar Texts - சி. சங்கீதா / S. Sangeetha (International Journal of Tamil Language and Literary Studies)
Tamil is one of the classical languages with ancient grammar texts. Grammar helps to speak and write a language without mistakes. Tamil Grammar is divided into five categories namely Yeluthu (Alphabet), Sol (Word), Porul (Meaning), Yappu (Texture) and Ani (Figures of Speech). “Tolkappiyam” is considered a unique grammatical and life-oriented text that enriches grammar and its categories in a detailed manner. Among the grammar books available in Tamil, “Tolkappiyam” is the oldest book that best deals with the theory of grammar. No grammar books were written for many years, once the “Tolkappiyam” was published. Even though the works “Veerachozhiyam” and “Neminatham” explain Tamil grammar rules by blending with the Sanskrit language. After them, “Nannool”, the grammar book that appeared in the Tamil language, in which Bhavanandiyar mentions the development of the language and the innovation that occurred from time to time. The books such as “Prayoga Vivekam”, “Elakkana Vilakkam”, “Tonnool Vilakkam”, “Muthu Viriyam”, “Swaminatham” have been written following Bhavanandiyar’s explanation. However, many concepts are the same and some are different in these books. “Tolkappiyam”, which is a primary grammar book has divided the types of words into four types. Among them, one is a morpheme, when it depends on the name without its object, it takes the noun object and when it depends on the verb, it takes its place with its object. Although it occurs in the middle of the language so it is called interjections because it often comes in between them. “Nannool” divides morphemes into eight categories whereas “Tolkappiyam” mentions it in seven categories. Among them, in Tolkappiyam’s Solladikaram - Interjection, the three types such as those that give meaning in their own (Tham Kuruppil Porul Unarthuvana, Acai-nilai (something) and Icai-Niṟai (an expletive used to fill a gap in the metre of a rhyme) are explained in detail. Thus, this article examines interjections and the types of interjections how they have been studied in other grammar texts their importance and uniqueness.